Pengembangan Media Alat Peraga Tiga Dimensi (3D) pada Pembelajaran IPAS Materi Gerhana Matahari untuk Siswa Kelas VI Madrasah Ibtidaiyah - SISKA NUR WAHIDA (Program Studi PGMI IAI Pangeran Diponegoro Nganjuk, 2026)
ABSTRACT Understanding the concept of a solar eclipse often presents challenges for elementary school students due to its abstract nature. Therefore, the development of concrete and interactive learning media is needed to facilitate students’ conceptual understanding. This study aims to develop a three-dimensional (3D) solar eclipse teaching aid for IPAS learning among sixth-grade students at MI Miftahul Huda Semboro and to examine its feasibility and effectiveness in enhancing students’ learning interest. The research employed a Research and Development (R&D) approach using the 4D model, which consists of the stages of define, design, develop, and disseminate. Data were collected through observations, interviews, documentation, and questionnaires involving teachers and students as research participants. The evaluation focused on two aspects, namely media quality and material suitability. The results revealed that the material expert validation obtained a percentage score of 85.45%, indicating that the teaching aid was categorized as valid and suitable for use in learning activities. Meanwhile, media expert validation achieved a score of 88.89%, which also fell within the valid category. Student responses showed positive perceptions of the teaching aid and confirmed its practicality in classroom learning. Furthermore, the implementation of the 3D solar eclipse teaching aid increased students’ engagement, attention, and enthusiasm during lessons. The media also helped students visualize the positions and movements of the Earth, Moon, and Sun during a solar eclipse, resulting in improved understanding and learning outcomes. Therefore, the developed 3D teaching aid can serve as an effective and innovative learning medium for teaching solar eclipse concepts in elementary science education. Keywords: 3D Teaching Aid, Solar Eclipse, IPAS Learning, Learning Media Development, Elementary Education.